Sistem Pakar Untuk Screening Awal Pada Gangguan PTSD (Post Traumatic Stress Disorder) Menggunakan Metode Forward Chaining Berbasis Website - Muhammad Faisal Dzaki Sidik; Budi Apriyanto (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Bad experiences in a person have different stories, ranging from small things to those that make it hard to forget and greatly affect his psychology to an indeterminate extent because bad experiences are easier to remember than good or pleasant experiences even though Some say that good or pleasant experiences are difficult to forget, but in fact, it is the bad experiences that are very difficult to forget which in the end only imagines in his mind and makes him suffer from psychological disorders. These psychological disorders make it difficult for a person to forget and make him remember continuously which makes him panic, stressed, and traumatized. This person may experience PTSD (Post Traumatic Stress Disorder) or post-traumatic stress disorder, or someone who previously experienced a bad or unpleasant event or experience. It is still unknown how many people know about PTSD (Post Traumatic Stress Disorder), maybe people only know about trauma, then there is a lack of education or information about PTSD (Post Traumatic Stress Disorder) disorders which makes people not realize that they are affected by these disorders, which in the end people only find out when they or those closest to them have experienced PTSD (Post Traumatic Stress Disorder) disorders, and many people still don't know how the solution is to find out if they are indicated by PTSD (Post Traumatic Stress Disorder), which makes these people not know that they could have indications of PTSD (Post Traumatic Stress Disorder). From these problems, a solution was created, namely the PTSD Initial Screening website (Post Traumatic Stress Disorder). In making the Initial Screening website, researchers used a method, the method used is the Forward Chaining method. The result of this study is a website for early screening of PTSD (Post Traumatic Stress Disorder) disorders, which can help the public to know whether they are indicated or not about PTSD (Post Traumatic Stress Disorder) disorders.